Balancing workload, motivation and job satisfaction in Rwanda: assessing the effect of adding family planning service provision to community health worker duties. Issue 1 (December 2015) - Chin-Quee, Dawn; Mugeni, Cathy; Nkunda, Denis; Uwizeye, Marie; Stockton, Laurie; Wesson, Jennifer
Abstract Background Task shifting from higher cadre providers to CHWs has been widely adopted to address healthcare provider shortages, but the addition of any service can potentially add to an already considerable workload for CHWs. Objective measures of workload alone, such as work-related time and travel may not reflect howCHWs actually perceive and react to their circumstances. This study combined perception and objectivemeasures of workload to examine their effect on quality of services, worker performance, and job and clientsatisfaction. Methods Three hundred eighty-three CHWs from control and intervention districts, where the intervention group was trained to provide contraceptive resupply, completed diaries of work-related activities for one month. Interviews were also conducted with a subset of CHWs and their clients. Results CHW diaries did not reveal significant differences between intervention and control groups in time spent on service provision or travel. Over 90 % of CHWs reported workload manageability, job satisfaction, and motivation to perform their jobs. Clients were highly satisfied with CHW services and most stated preference for future services from CHWs. Conclusion The study demonstrated that adding resupply of hormonal contraceptives to CHWs' tasks would not place undue burden on them. Accordingly, the initiative was scaled up in all 30 districts in the country.